Faktor Karakterıstık Audıt, Karakterıstık Perusahaan Dan Kepemılıkan Manajerıal Terhadap Peralıhan Kantor Akuntan Publık Pada Perusahaan Yang Terdaftar Dı Bursa Efek Indonesıa - Supriyanto Supriyanto; Mareta Frisilia (Universitas Internasional Batam, 2021)
This research is to analyze the factors that trigger the change of PAF. Audit opinion, audit delay, PAF scale are categories of audit characteristics and management changes, financial distress, company scale including company characteristics and managerial ownership as research factors. The final research summarizes that management exchanges, company scale, and audit delays have no effect on the change PAF. Audit opinion and managerial ownership have a negative effect on the change PAF, financial distress and the PAF scale have a positive effect on the change PAF. The company is facing financial problems and a big PAF will cause a change.